Ultrasound-Guided Transversalis Fascia Plane Block Versus Transversus Abdominis Plane Block for Postoperative Analgesia After Repeat Cesarean Delivery: A Prospective Observational Study - Taha Emre Ötügen; Fethi Akyol; Talha Karataş; Gamze Ataş; Hakan Gökalp Taş; Ufuk Kuyrukluyıldız (Healthcare, 2026)
Background: Effective postoperative pain control after cesarean delivery is essential for facilitating early mobilization and reducing analgesic requirements. Ultrasound-guided fascial plane blocks, such as the transversus abdominis plane (TAP) and transversalis fascia plane (TFP) blocks, are increasingly used as components of multimodal analgesia; however, direct comparative data between these techniques remain limited. Methods: In this prospective observational study, 90 patients undergoing repeat cesarean deliveries under spinal anesthesia were administered either a bilateral ultrasound-guided transversus abdominis plane (TAP) block or a transversus fascia plane (TFP) block in accordance with standard clinical practice. The intensity of postoperative pain, assessed both at rest and during movement, was determined using VAS scores at 3, 6, 12, and 24 h after surgery. The time until first ambulation and additional postoperative analgesic consumption beyond the standardized baseline analgesic regimen over the first 24 postoperative hours were also evaluated. Results: The patients who were administered a TFP block had diminished postoperative pain levels, reduced additional postoperative analgesic requirements, and expedited mobilization relative to those administered a TAP block. The TFP group had considerably lower movement-related pain levels within the first 24 h following surgery. Opioid-related adverse effects were comparable between groups. Conclusions: After a repeat cesarean delivery, applying a TFP block was linked to better postoperative analgesia and fewer analgesic requirements than applying a TAP block. These findings suggest that TFP blocks may represent an effective component of multimodal analgesia in obstetric anesthesia.